2018
DOI: 10.1111/1348-0421.12657
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological response of mice to intranasal inoculation with Lactococcus lactis expressing Group A Streptococcus antigens, to be used as an anti‐streptococcal vaccine

Abstract: Protein subunit vaccines are often preferred because of their protective efficacy and safety. Lactic acid bacteria expressing heterologous antigens constitute a promising approach to vaccine development. However, their safety in terms of toxicity and bacterial clearance must be evaluated. Anti-Streptococcus pyogenes (S. pyogenes) vaccines face additional safety concerns because they may elicit autoimmune responses. The assessment of toxicity, clearance and autoimmunity of an antistreptococcal vaccine based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…2.7), a quarter of each implanted scaffold was weighed, resuspended in 0.5 mL phosphate buffered saline (PBS) vortexed for 2 min, serially diluted and seeded for further CFU counting. For species determination, isolated colonies were identified by MALDI-TOF Mass Spectrometry (Bruker Daltonik) as previously published 62 . The colonies were identified according to the database provided by the manufacturer: MALDI Biotyper library v4.0 5.627 MSP using the MALDI Biotyper 3.1 software package (Bruker Daltonik), using default settings.…”
Section: Methodsmentioning
confidence: 99%
“…2.7), a quarter of each implanted scaffold was weighed, resuspended in 0.5 mL phosphate buffered saline (PBS) vortexed for 2 min, serially diluted and seeded for further CFU counting. For species determination, isolated colonies were identified by MALDI-TOF Mass Spectrometry (Bruker Daltonik) as previously published 62 . The colonies were identified according to the database provided by the manufacturer: MALDI Biotyper library v4.0 5.627 MSP using the MALDI Biotyper 3.1 software package (Bruker Daltonik), using default settings.…”
Section: Methodsmentioning
confidence: 99%
“…gmLAB based on intracellular production have been reported, and mucosal administration has shown to have desirable effects (Liu et al 2018). In addition, previous studies have shown that nasally administered gmLAB cleared more than 24 h after administration (Garcia et al 2018). These results suggest that the administered gmLAB either rupture or are phagocytosed by immune cells and leak intracellular proteins.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have shown that the sublingual route with CTB or heat-labile toxin can generate IgA at mucosal sites and serum IgG to protective levels against other species of Streptococci [10,11]. Several studies have demonstrated intranasal immunization can generate a mucosal immune response against GAS [14,16,25], but ours is the first study to show that a response can also be generated through immunization with a subunit vaccine by the sublingual route, which has potential safety benefits over intranasal immunization.…”
Section: Discussionmentioning
confidence: 83%
“…Whole cell vectors such as Lactococcus lactis, or cell-like structures could potentially bypass the need for adjuvant systems. A study with L. lactis expressing M-protein units was able to produce serum IgG and pharyngeal IgA without the need for adjuvant through the intranasal route [25]. Oral gavage of L. lactis expressing pilin proteins was also able to stimulate a bronchial IgA response as well as a serum IgG response, demonstrating the benefit of cellular structures in mucosal immunity [15].…”
Section: Discussionmentioning
confidence: 99%